2006
DOI: 10.1073/pnas.0510946103
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate histone deacetylation during oocyte meiosis causes aneuploidy and embryo death in mice

Abstract: Errors in meiotic chromosome segregation are the leading cause of spontaneous abortions and birth defects. Almost all such aneuploidy derives from meiotic errors in females, with increasing maternal age representing a major risk factor. It was recently reported that histones are globally deacetylated in mammalian oocytes during meiosis but not mitosis. In the present study, inhibition of meiotic histone deacetylation was found to induce aneuploidy in fertilized mouse oocytes, which resulted in embryonic death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 37 publications
11
134
1
3
Order By: Relevance
“…For mice, the above lysine residues on H3 and H4 are acetylated in GV oocytes. However, with the resumption of meiosis, deacetylation was observed in MII oocytes, with the exception of H4K8ac which was reported present or absent regarding acetylation [40,41]. For humans, H4K5, H4K8, H4K12 and H4K16 were acetylated in GV oocytes, while partial deacetylation in MII oocytes was shown [42].…”
Section: Histone Acetylationmentioning
confidence: 93%
See 3 more Smart Citations
“…For mice, the above lysine residues on H3 and H4 are acetylated in GV oocytes. However, with the resumption of meiosis, deacetylation was observed in MII oocytes, with the exception of H4K8ac which was reported present or absent regarding acetylation [40,41]. For humans, H4K5, H4K8, H4K12 and H4K16 were acetylated in GV oocytes, while partial deacetylation in MII oocytes was shown [42].…”
Section: Histone Acetylationmentioning
confidence: 93%
“…Inadequate histone deacetylation during mouse oocyte meiosis may cause aneuploidy and embryo death. On the other hand, old mouse oocytes have higher levels of acetylation at H4K8 and H4K12 when compared to that of young oocytes [40]. Similar to old mouse oocytes, it has been reported that defective deacetylation of H4K12 in human oocytes is associated with advanced maternal age as well as chromosome misalignment [42].…”
Section: Epigenetic Changes: Underlying Mechanisms Of Oocyte Agingmentioning
confidence: 93%
See 2 more Smart Citations
“…Mice are generally retired from breeding around 9 months of age [27]; however, females are still capable of ovulating and carrying offspring, albeit at a lower frequency than their younger counterparts. Previous reports have been successful in stimulating and collecting metaphase II oocytes from mice ranging from 10 to 16 months of age [7,15,[28][29][30][31]. B6D2F1 mice are considered exceptional breeders, as females regularly produce large litters (JAX® Mice; Jackson Laboratory, Bar Harbor, ME) and have a long lifespan of approximately 26 months on average (Harlan Laboratories, Indianapolis, IN).…”
Section: Animalsmentioning
confidence: 99%